Analisis dan Perancangan Sistem Manajemen Prospek Pelanggan Dengan Model Sales Pipeline pada PT. Supratama Prima Nusantara (Biznet Networks) Branch Malang - Mokhammad Pungky Fadhli; Retno Indah Rokhmawati; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In order to competing and getting a lot of customers, the company must pay attention to many factors. One of them, in an effort to increase the sales volume of the company should refer to various factors that are closely related to salesman which is the company's spearhead in marketing and product sales. So be considered if the company wants to win many deals with prospects and achieve sales targets as well as support salesman and salesman activities related to sales with a CRM (Customer Relationship Management) application, that is Customer Prospect Management System that is able to present customer data and sales stage so know whether The prospect qualifies to become a customer or not by using the Sales Pipeline model. This research using an object-oriented approach. The purpose of this research is to modelling the business processes, analyzing requirements specification and system design, and evaluate the result of the specification requirements. To illustrate the class modeling, interactions, data, and user interface requirements specification using prototype evaluation and chronological matrix. The evaluation results in this study showed that the grooves were made by two respondents after a test use case scenarios are in accordance with the mechanism should be. Then traceability evaluation results show that each requirement has a unique code that can be traced to the features, needs and the model diagram.